Peculiar alignment and strain of 2D WSe2 grown by van der Waals epitaxy on reconstructed sapphire surfaces. (4th September 2019) - Mortelmans, Wouter; El Kazzi, Salim; Nalin Mehta, Ankit; Vanhaeren, Danielle; Conard, Thierry; Meersschaut, Johan; Nuytten, Thomas; De Gendt, Stefan; Heyns, Marc; Merckling, Clement
Abstract: The increasing scientific and industry interest in 2D MX2 materials within the field of nanotechnology has made the single crystalline integration of large area van der Waals (vdW) layers on commercial substrates an important topic. The c-plane oriented (3D crystal) sapphire surface is believed to be an interesting substrate candidate for this challenging 2D/3D integration. Despite the many attempts that have been made, the yet incomplete understanding of vdW epitaxy still results in synthetic material that shows a crystallinity far too low compared to natural crystals that can be exfoliated onto commercial substrates. Thanks to its atomic control and in situ analysis possibilities, molecular beam epitaxy (MBE) offers a potential solution and an appropriate method to enable a more in-depth understanding of this peculiar 2D/3D hetero-epitaxy. Here, we report on how various sapphire surface reconstructions, that are obtained by thermal annealing of the as-received substrates, influence the vdW epitaxy of the MBE-grown WSe2 monolayers (MLs). The surface chemistry and the interatomic arrangement of the reconstructed sapphire surfaces are shown to control the preferential in-plane epitaxial alignment of the stoichiometric WSe2 crystals. In addition, it is demonstrated that the reconstructions also affect the in-plane lattice parameter and thus the in-plane strain of the 2D vdW-bonded MLs. Hence, the results obtained in this work shine more light on the peculiar concept of vdW epitaxy, especially relevant for 2D materials integration on large-scale 3D crystal commercial substrates.